The rs1940475 polymorphism in the MMP8 gene as a protective factor of severe breast cancer - N. V. Pavlova; I. V. Ponomarenko; M. I. Churnosov (Акушерство, гинекология и репродукция, 2022)
Aim: to investigate an association between polymorphism in the MMP2, MMP8, MMP9 genes and severe breast cancer (BC).Materials and Methods. Retrospective comparative study was conducted by assessing a cohort of 345 BC patients: 254 patients at stage I–II and 91 at stage III–IV. Genotyping of the three single nucleotide polymorphisms in the MMP2 (C>T rs243865), MMP8 C>T rs1940475), and ММР9 (C>T rs3918242) genes was performed. A comparative analysis of the genetic characteristics of patients with stage I–II and stage III–IV of the disease was performed.Results. The allele variant T rs1940475 (C>T) of the MMP8 gene in BC patients at stage I–II (0.512) was found by 1.2-fold more often compared with patients at stage III–IV of the disease (0.428; pperm = 0.05). According to allelic (odds ratio (OR) = 0.71; 95 % confidence interval (CI) = 0.51–1.00; pperm = 0.05) and additive (OR = 0.69; 95 % CI = 0.48–0.99; pperm = 0.05) genetic models, the allele T rs1940475 (C>T) of the MMP8 gene has protective effect for developing stage III–IV BC. The polymorphic locus rs1940475 (C>T) determines the amino acid substitution in the MMP8 protein (p.K87E) and DNA binding to the transcription factors NF-AT1, MYC and CIZ, is associated with the expression of the genes MMP27 and RP11-817J15.3 acting as an enhancer regulatory site in primary breast epithelial cells. Single nucleotide polymorphism in the MMP2 (C>T rs243865), ММР9 (C>T rs3918242) genes is not associated with severe BC (stages III–IV).Conclusion. The single nucleotide polymorphism rs1940475 in the MMP8 gene is a protective factor protecting against severe BC course.